GPER and Testicular Germ Cell Cancer - Chevalier, Nicolas; Hinault, Charlotte; Clavel, Stephan; Paul-Bellon, Rachel; Fenichel, Patrick (Frontiers in Endocrinology, 2021)
The G protein-coupled estrogen receptor (GPER) is a widely conserved 7-transmembrane-domain protein which has been identified as a novel 17a-estradiol-binding protein that is structurally distinct from the classic oestrogen receptors (ERa and ERb). There are still conflicting data regarding the exact role and the natural ligand of GPER in reproductive tracts as both male and female knock-out mice are fertile and have no abnormalities of reproductive organs. Testicular germ cell cancers (TGCCs) are the most common malignancy in young males and the most frequent cause of death from solid tumors in this age group. Clinical and experimental studies suggested that estrogens, the archetype of female hormones, participate in the physiological and pathological control of male germ cell proliferation. In human seminoma cell line, 17a-estradiol (E2) inhibits in vitro cell proliferation through an ERb-dependent mechanism. In contrast, E2 coupled to BSA (E2-BSA), an impermeable E2 conjugate, stimulates in vitro cell proliferation by activating ERK1/2 and protein kinase A through a membrane GPCR that we further identified as GPER. The same effect was observed with low but environmentally relevant doses of BPA, an estrogenic endocrine disrupting compound. Furthermore, GPER is specifically overexpressed in seminomas but not in non-seminomas and this overexpression is correlated with an ERb-downregulation. This GPER overexpression could be linked to some genetic variations, as single nucleotide polymorphisms, which was also reported in other hormone-dependent cancers. We will review here the implication of GPER in TGCCs pathophysiology and the arguments to consider GPER as a potential therapeutic target in humans.